Asthma remission: Predicting future airways responsiveness using an miRNA network - McGeachie, Michael J.; Davis, Joshua S.; Kho, Alvin T.; Dahlin, Amber; Sordillo, Joanne E.; Sun, Maoyun; Lu, Quan; Weiss, Scott T.; Tantisira, Kelan G. (Journal of allergy and clinical immunology, 2017)
MicroRNA extraction, preparation, post-PCR data processing, and quality control have been previously described and the data accessible on the National Center for Biotechnology Information Gene Expression Omnibus under accession GSE74770,2 although we use here a detection threshold of 75% of the 160 subjects plus 13 replicates (173 total) as a minimum criteria for including miRNAs in our analysis. Analysis of miR-deep sequencing data7 showed that miR-30a is among the most abundant miRs expressed in the human primary ASM cells. Because other miR-30 family members (miR-30d, miR-30e) are also highly expressed in ASM cells, we transfected mimics of these miRs in ASM cells and examined their effects on ASM growth and hypertrophy in vitro. [...]miR-30a, miR-30d, and miR-30e all significantly increased the size of ASM cells (P < .01; see Fig E5 in this article's Online Repository at www.jacionline.org), FAS, HIPK3, IL10, MAPK9, MYLIP, PTEN, RB1, RBL2, RUNX1, RUNX3, SIRPA, SLC2A3, STAT3, TGFBR2, TIMP2, VEGFA hsa-miR-126-5p ADAM9, CXCL12, MMP7, MYC, PTPN7, SLC45A3 hsa-miR-1290 - hsa-miR-146b-5p HNRNPD, IRAK1, KIT, MMP16, NFKB1, PDGFRA, TLR4, TRAF6, UHRF1 hsa-miR-17-5p ADAR, APP, BCL2, BCL2L11, BMP2, BMPR2, CCL1, CCND1, CCND2, CDKN1A, CLU, DNAJC27, DNMT1, E2F1, EPAS1, ETV1, FBXO31, GPR137B, HBP1, HIF1A, HSPB2, ITGB8, JAK1, KAT2B, LDLR, MAP3K12, MAPK9, MDM2, MEF2D, MMP2, MYC, NABP1, NCOA3, NPAS3, NPAT, PDLIM7, PHLPP1, PKD2, PTEN, PTPRO, RB1, RBL1, RBL2, RND3, RUNX1, SIRPA, SMAD4, SMURF1, SOCS6, STAT3, TBC1D2, TCEAL1, TCF3, TGFBR2, TIMP3, TNFSF12, TP53INP1, UBE2C, VEGFA, WEE1, YES1, ZBTB4, ZNFX1 hsa-miR-185-5p ALOX12, AQP3, AR, ARC, ATR, CAMK4, CASP14, CDC42, CDK6, DNMT1, DUSP4, EPAS1,...